2004
DOI: 10.1002/jmv.20009
|View full text |Cite
|
Sign up to set email alerts
|

Increased detection of rotavirus using a real time reverse transcription‐polymerase chain reaction (RT‐PCR) assay in stool specimens from children with diarrhea

Abstract: Six-hundred and twenty-six stool specimens collected from children with diarrhea over a 12-month period were tested for rotavirus using a real time reverse transcription-polymerase chain reaction (RT-PCR) assay, a conventional nested PCR assay and by electron microscopy (EM). A fragment of 87 bp in a highly-conserved region of non-structural protein 3 (NSP3) in rotavirus genome was amplified by a single-step RT-PCR protocol in a closed-tube system. Rotavirus was detected in 123 samples (20%) with the real time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
112
1
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(125 citation statements)
references
References 28 publications
4
112
1
8
Order By: Relevance
“…19 This would provide firmer information on the incidence of this condition and would allow definitive strain characterisation 20 in this group.…”
Section: Discussionmentioning
confidence: 98%
“…19 This would provide firmer information on the incidence of this condition and would allow definitive strain characterisation 20 in this group.…”
Section: Discussionmentioning
confidence: 98%
“…These findings indicate the high reproducibility in viral load quantitation by the assay. Two common gastroenteritis-associated viruses, sapovirus and group A rotavirus, were detected in parallel, as previously described (4,6).…”
Section: The Studymentioning
confidence: 99%
“…Similarly, Pang et al (2004) reported that Real-Time PCR targeting the RVA NSP3 gene, using TaqMan system, was 1,000-fold more sensitive than conventional RT-PCR.…”
Section: Discussionmentioning
confidence: 97%